2014
DOI: 10.1039/c4en00039k
|View full text |Cite
|
Sign up to set email alerts
|

The yin: an adverse health perspective of nanoceria: uptake, distribution, accumulation, and mechanisms of its toxicity

Abstract: This critical review evolved from a SNO Special Workshop on Nanoceria panel presentation addressing the toxicological risks of nanoceria: accumulation, target organs, and issues of clearance; how exposure dose/concentration, exposure route, and experimental preparation/model influence the different reported effects of nanoceria; and how can safer by design concepts be applied to nanoceria? It focuses on the most relevant routes of human nanoceria exposure and uptake, disposition, persistence, and resultant adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
92
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 127 publications
(393 reference statements)
8
92
0
Order By: Relevance
“…[28,29] In the case of nanoceria, a larger ratio of surface area to volume leads to a larger surface Ce 3+ /Ce 4+ ratio, which could be related to a higher toxicity for smaller ceria NPs. [6] However, this is not always applicable for all ceria materials. In fact, a study demonstrated that larger ceria particles can have a higher toxicity towards eukaryotic cells.…”
Section: Toxicity Of Nanoceriamentioning
confidence: 99%
See 2 more Smart Citations
“…[28,29] In the case of nanoceria, a larger ratio of surface area to volume leads to a larger surface Ce 3+ /Ce 4+ ratio, which could be related to a higher toxicity for smaller ceria NPs. [6] However, this is not always applicable for all ceria materials. In fact, a study demonstrated that larger ceria particles can have a higher toxicity towards eukaryotic cells.…”
Section: Toxicity Of Nanoceriamentioning
confidence: 99%
“…[50] These different reports demonstrated various protective as well as toxic effects for nanoceria, as already pointed out in other reviews on other nanomaterials as well. [6,28,32,51] Furthermore, the combination of materials, for example the use of nanoceria with other particles such as those in diesel exhaust, may increase their toxicity [52] and render the biosafety of nanoceria more challenging to determine. Table 1 lists representative examples of all reported effects of nanoceria materials according to their preparation method, size, and the tested organism.…”
Section: Toxicity Of Nanoceriamentioning
confidence: 99%
See 1 more Smart Citation
“…Of critical importance are the redox properties of ceria which enables it to transition between Ce (III) and Ce (IV), which are the key to understanding its potential toxicity. 7 While there has been somewhat extensive investigation into the mammalian toxicity of ceria (as well as it's therapeutic uses), 8 based on the present review, there has been considerably less effort invested into investigation of the environmental fate and effects of nanoceria. In this critical review, we discuss the likely points of environmental release along product life-cycles and resulting environmental exposure to nanoceria, methods of detection in the environment, fate and transport, as well as the available toxicity literature for ecological receptor species.…”
Section: Introductionmentioning
confidence: 99%
“…A more chemically flexible nanoparticle production approach is mechanical attrition of a bulk material into small particles in a ''top down'' approach [6] like rotary mills, but this process has inherent limitations with regard to input material. If insoluble particles are formed in situ within a fluid, the airborne release of particles is minimized, lessening the risk of environmental contamination [7][8][9][10] and respiratory distress, [11] while concurrently inhibiting agglomeration. The addition of cavitation to in situ approaches can enhance particle formation and enhance the wettability of particles.…”
mentioning
confidence: 99%